2009
DOI: 10.1007/s10916-009-9357-7
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Clinical Pathway in Coronary Artery Bypass Surgery

Abstract: Few studies have been devoted to the exploration of the effect of clinical pathways on coronary artery diseases treated with coronary artery bypass (CAB) surgery. This study was aimed to investigate the cost and effectiveness of the clinical pathway on CAB surgery in a medical center. With a retrospective dataset in 2003-2007, 212 CAB surgery patients were included. Data of the costs and postoperative complication occurrence and length of stays were the focus and patient demographics, surgical risk indicator E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…In more recent years, only a few studies have assessed the cost-effectiveness of integrated care pathways, and among these studies, the patient groups and settings where the pathways were implemented, vary widely. [ 25 29 ]…”
Section: Introductionmentioning
confidence: 99%
“…In more recent years, only a few studies have assessed the cost-effectiveness of integrated care pathways, and among these studies, the patient groups and settings where the pathways were implemented, vary widely. [ 25 29 ]…”
Section: Introductionmentioning
confidence: 99%
“…Both type 1 and type 2 diabetes can increase hip fracture risk and complications due to abnormal bone metabolism [ 4 , 5 ]. Vestergaard found that compared with those without diabetes, the relative risk (RR) for hip fractures in patients with type 1 diabetes was 6.94, and that for hip fractures in patients with type 2 diabetes was 1.38 [ 6 ]. In other studies, patients with longer diabetes duration were associated with a higher hip fracture risk compared to patients without diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…One important issue for all fast‐track protocols or CPs is the concern for increased complications or hospital readmission. CPs for CABG patients have been shown to be safe, and have not caused an increase in the rate of postoperative complications (Lin, Chen, Tsai, Chiao, & Lin, ). Additionally, early discharge of patients does not lead to an increase in readmission rates (El Baz, Middel, Van Dijk, Boonstra, & Reijneveld, ; van Mastrigt et al., ).…”
Section: Discussionmentioning
confidence: 99%